Assessment of an ELISA method to support surveillance of bovine tuberculosis in Albania. Issue 1 (December 2015) - Koni, Anita; Juma, Arla; Morini, Matteo; Nardelli, Stefano; Connor, Robert; Koleci, Xhelil
Abstract Background Bovine tuberculosis (bTB) is an important bacterial infectious disease in Albania of concern to animal and human health; its prevalence is poorly documented. Methods In this longitudinal study, we tested by ELISA 2661 serum samples, from 154 herds, with the aim of establishing the suitability of this approach to screen the bovine population for bTB. In a follow-on survey of 87 animals in three villages, we assessed the usefulness of theMycobacterium bovis IDEXX ELISA (IDEXX M. bovis Antibody (Ab) Test. IDEXX Europe B.V P.O. Box 1334, 2130 EK Hoofddorp, The Netherlands) assay by comparing IDEXX results with the results of the single intradermal cervical skin test. Skin tests were performed either after or at the time of collection of blood samples, and therefore cattle were not sensitized by tuberculin before serological testing. Results The proportion of herds in which serologically positive cattle were found was 18.2 % (95 % CI, 1.9–25.8 %) and the prevalence of seropositive cattle was 1.4 % (95 % CI, 0.8–2.1 %). In the follow-up study, two of the 87 animals reacted positively to the skin test and two produced inconclusive reactions. No overlap was found between the four animals with positive IDEXX ELISA results and the four animals with non-negative skin test results. Conclusion The lack of agreement between the results of the two tests may reflect different elements of the immune response (humoral and cell-mediated immunity). In future, cattle should be sensitized by the intradermal injection of tuberculin 14 days prior to the collection of blood samples, which would then be tested by theMycobacterium bovis IDEXX ELISA Test in order to determine more accurately the prevalence of infection.